Individual Feed Efficiency Monitoring of Charolaise Candidate Young Bulls in Relation to Feeding Behavior and Self-Performance Test Results - Gabriella Holló; Henrietta Nagy-Kiszlinger; János Tossenberger; Márton Török; Balázs Húth (Animals, 2021)
This study evaluated the effect of differences in residual feed intake (RFI) of Charolaise candidate young bulls on feeding behavior and self-performance test results. Bulls were classified into high and low RFI (H-RFI, L-RFI) groups. Bulls were fed in a HOKOFARM system to measure individual animal intake and behavior. L-RFI bulls had significantly lower feed intakes (p = 0.002) and higher gain to feed ratio (p = 0.001), lower intake per day/kg DM (dry matter) (p = 0.002) and lower intake g/body weight/day (p < 0.001). L-RFI animals had lower visits number per day (p = 0.02), but spent longer time per visit (p = 0.02), and tended to have higher intake g/visit (p = 0.06) on feeders. The correlation between RFI and DMI (dry matter intake)/bodyweight/day as well as intake per day/kg were large and positive. Back-loin length and rump length, and moreover muzzle width and frame, showed negative correlations with RFI value. However, bulls with better RFI values associated with lower legs score. Results reveal that RFI was shown beneficial correlations with economically relevant self-performance traits. Further investigations are needed to seek additional indicator traits that are predictive for RFI.